High-speed domain wall racetracks in a magnetic insulator - Saül Vélez (Nature Portfolio, 2019)
Fast and low-power electrical control of magnetic textures is expected to enable a new generation of computational devices. Here the authors show how chiral interactions determine the structure of domain walls in Tm3Fe5O12 and lead to efficient current-driven wall motion.